MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MELALUI MEDIA GAMBAR BAGI ANAK TUNAGRAHITA SEDANG DI SDLB BHAKTI LUHUR MALANG - Maria Vianti Desa (Jurnal Pelayanan Pastoral, 2023)
Everyone has the right to have the opportunity to learn, because by learning to read people will be able to understand and understand well. Reading is a complex ability as a whole psychological process and skills development. Reading is a process of recognizing words, understanding words, and a skill that must be possessed by children. Beginning reading is an activity where the child cannot read yet, it is necessary to introduce letters. Opportunities to learn to read are open to everyone, including children with moderate mental retardation. The condition of being mentally retarded is moderate, in receiving and capturing information affecting reading ability at SDLB Bhakti Luhur Malang class C1. There are 3 mentally retarded children who can't read yet. The steps taken are to train reading beginners using picture media. The goal is to prove that through the media of images can improve the beginning reading ability of moderately mentally retarded children. This type of research is an experimental design used pre-experiment in the form of one group pretest-posttest. This research was conducted at SDLB Bhakti Luhur Malang class C1 which consisted of 3 moderately mentally retarded children. The results obtained after being given treatment for 3 mentally retarded children experienced an increase in beginning reading, namely FD, obtaining an average of 17.5% for imitating, matching, recognizing letters and spelling syllables. AB, obtain an average value of 25% practice imitating, matching, recognizing letters and spelling syllables. CE, obtained an average score of 27.5% in imitating, matching, recognizing letters and spelling syllables.